Marketing Strategy of Shrimp Paste Home Industry in Muarabaru Village, Cilamaya Wetan District, Karawang Regency - Lutfiah Qudsi Sekar Ayu; Abubakar; Yeni Sari Wulandari (Grouper, 2024)
Shrimp paste by home industry in Muarabaru Village, Cilamaya Wetan Subdistrict, Karawang Regency often faces problems especially in its marketing strategy, including simple packaging, unstrategic location, and limited promotion. The purpose of this research is to analyze the business model and design a new marketing strategy for the shrimp paste by home industry in Muarabaru Village. This research uses a qualitative approach with Business Model Canvas (BMC) and quantitative with Blue Ocean Strategy (BOS). The sampling technique was purposive sampling with 38 respondents consisting of business actors, retail traders, consumers, and experts. This study found that the shrimp paste by home industry in Muarabaru Village needs to improve, reduce, and create its marketing strategy. The most important thing to improve is the strategy of providing electronic payment tools such as banks and digital wallets to facilitate the transaction process with a score of 3.49. The most important thing to reduce is the strategy of maintaining discounts with a score of -1.46. The most important thing to create is a strategy to provide educational tourism facilities for making shrimp paste with a score of 4.52. It can be concluded that home industry in Muarabaru Village need to be more open about the times and technological advances to develop their business.